(3JhVjM GdeSGFd GdJi ChOYgG GHf HWdGf aj QSGdI OYhI GdCWHGAs - (3CHhGdMSf Ydj Hf gHI Gddg Hf GdShOi CKQOis; (3GHf HWdGf , GdeNJGQ Hf GdMSf Hf YHOhf, CHh GdMSf,J (B458 (3g` s
(3BNQgG (B:s
(3fbdJ ef fSNI SbjeI hUMMJ HbOQ GdEecGf s
(3fbdJ ef fSNI SbjeI hUMMJ HbOQ GdEecGf heY gPG dG JNdh gPg GdfSNI ef GdSbGeIs
(3gi CSFdI SCdgG EjGg CMO JdGejPgs
(3JHUQI GdYfhGf (B:s
(3JaSjQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B191 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B210s
Keywords: (3GdCOHs